2023
DOI: 10.48077/scihor9.2023.143
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of wildfires forecast performance in Albania: Case study

Orjeta Jaupaj,
Alban Doko,
Ardit Dervish
et al.

Abstract: The harmful impacts of climate change caused by wildfires are substantially harming the people of mainland Europe, as well as damaging species biodiversity and the ecosystem. It can be minimised by improving the effectiveness of fire risk forecasting and mitigation strategies. The aim of this paper was to investigate the accuracy of forest fire forecasts in Albania produced by the FWI (Fire Weather Index) system. During the summer of 2022, observations and data were collected on expected and actual fires in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…They note that the concept of "sustainability" in natural resource management is limited by nature's ability to regenerate and human adaptability, leading to a redefinition of the relationship between humans and nature in future generations. In other words, sustainability should not simply be about transferring resources and the environment to the next generation under the same conditions as in the present, but finding a way for future generations to adapt to it and also improve their standard of living 29) . Based on this, scholars have concluded that the success of forest development policies is significantly influenced by the rationality of socio-economicenvironmental arguments, as measured by the benefits that accrue to a particular community.…”
Section: Discussionmentioning
confidence: 99%
“…They note that the concept of "sustainability" in natural resource management is limited by nature's ability to regenerate and human adaptability, leading to a redefinition of the relationship between humans and nature in future generations. In other words, sustainability should not simply be about transferring resources and the environment to the next generation under the same conditions as in the present, but finding a way for future generations to adapt to it and also improve their standard of living 29) . Based on this, scholars have concluded that the success of forest development policies is significantly influenced by the rationality of socio-economicenvironmental arguments, as measured by the benefits that accrue to a particular community.…”
Section: Discussionmentioning
confidence: 99%